2006
DOI: 10.1021/ja0583721
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Probe Location in Reverse Micelles Determined by NMR Dipolar Interactions

Abstract: The location and interactions of solutes in microheterogeneous environments, such as reverse micelles, critically influence understanding of many phenomena that utilize probe molecules to characterize properties in chemical, biological, and physical systems. The information gained in such studies depends substantially on the location of the probe used. Often, intuition leads to the assumption that ionic probe molecules reside in the polar water pool of a system. In this work, the location of a charged polar tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
124
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 95 publications
(141 citation statements)
references
References 60 publications
17
124
0
Order By: Relevance
“…51 In the model system, line broadening of the PDC-V(V) signal was attributed to immobilization of the compound because proton 2D NOESY spectroscopy studies demonstrated that the protons on the aromatic ring were near the lipid tail group, and thus the complex penetrates the nonpolar layer. 51,52 In the studies with the SRvesicle, line broadening may also occur because of this type of interaction. However, because the concentration of lipid in the assay is small and the vanadium complex is in large excess, the lipid interaction in these preparations is not likely able to support the 4 mM PDC-V(V) complex used in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…51 In the model system, line broadening of the PDC-V(V) signal was attributed to immobilization of the compound because proton 2D NOESY spectroscopy studies demonstrated that the protons on the aromatic ring were near the lipid tail group, and thus the complex penetrates the nonpolar layer. 51,52 In the studies with the SRvesicle, line broadening may also occur because of this type of interaction. However, because the concentration of lipid in the assay is small and the vanadium complex is in large excess, the lipid interaction in these preparations is not likely able to support the 4 mM PDC-V(V) complex used in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Even in the micromolar range, oxovanadates can induce specific responses in enzymes such as phosphohydrolases 5,32,33 and, therefore, effects observed in vivo 20,[34][35][36][37][38] may be, in part, due to the action of species such as decavanadate (V 10 ), 38 vanadate monomer, 5 or vanadyl cation. 5,23,24,39 Combining biochemical kinetic studies with analysis by 51 V NMR spectroscopy, 9,11 it is possible to correlate inhibition with the presence of specific vanadate species as has previously been reported. 5,9,11,23,24,26 In the present study, the effects of three vanadium complexes, namely pyridine-2,6-dicarboxylatodioxovanadium(V) (PDC-V(V)), 16 bis(maltolato)oxovanadium(IV) (BMOV) 27 and an analogue of amavadine, bis(N-hydroxylamidoiminodiacetato)vanadium(IV) HAIDA-V(IV), 28 on SR Ca 2+ -ATPase activity were evaluated (Figure 1).…”
Section: +mentioning
confidence: 92%
“…characterization techniques originally developed for the characterization of proteins are useful for the characterization of repetitive peptides as well [63]. Protein concentrations of peptide-based biomaterials can be rapidly determined spectrophotometrically or colorimetrically or by using a Coomassie brilliant blue or bicinchonic acid assay.…”
Section: Biophysical Properties-manymentioning
confidence: 99%
“…In addition, an improved understanding of dynamical properties that elucidates the mass transport limitations and rate processes in mesoporous materials is still needed. Experimental efforts, including additional [17][18][19] complementary measurements that provide insight into solute location in nanoconfined solvents will, along with theoretical and simulation work, be critical to such efforts.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21] We have previously found in simple models that the position distributions of a proton transfer reactant complex and product complex differ and that this difference can play a role in the reaction mechanism. 14,15 Interestingly, Sedgwick et al have observed different locations of a photoacid in reverse micelles constructed with different surfactant molecules; 18 in reverse micelles, a solute can move not only within the water pool but also intercalate into the surfactant layer that represents the confining framework.…”
Section: Introductionmentioning
confidence: 99%